Disruption of Biofilm Formation by Dead Sea Soil Extracts: A Novel Approach Against Diabetic Foot Wound Isolates - Mohammad Zubair; Farha Fatima; Sumbul Rahman; Tariq Alrasheed; Roba Alatawy; M. Ahmed Mesaik (Microbiology Research)
Bacterial biofilms are closely associated with the rising threat of antimicrobial resistance, which is becoming a global concern. Recently, there has been increased interest in natural extracts as potential antimicrobial agents. One such extract is Dead Sea mud. While there is some evidence of its antimicrobial properties, it has not been extensively studied. Therefore, we designed a study to evaluate the potential of Dead Sea soil as an antimicrobial agent. For this purpose, three bacterial species (Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus) were isolated from the ulcerated foot of a patient in a hospital in Tabuk. P. aeruginosa exhibited significant antibiotic resistance, particularly to Levofloxacin (90%) and Tobramycin (80%), while S. aureus showed 70% resistance to Levofloxacin but no vancomycin resistance. Biofilm activity varied among bacterial strains, with P. aeruginosa showing 30% strong biofilm production. MIC values indicated resistance levels, with P. aeruginosa strain PA8 having the highest MIC at 650 µL/mL. All strains showed significant differences in exopolysaccharide (EPS) production at 0.25 × MIC (p ≤ 0.05) and 0.5 × MIC (p ≤ 0.005). Similarly, alginate production was significantly reduced at 0.25 × MIC (p ≤ 0.05), with even greater inhibition at 0.5 × MIC for combinations such as EC7 + SA5 (p ≤ 0.001). Hydrophobicity significantly changed at 0.25 × MIC (p ≤ 0.05), and combinations revealed highly significant reductions at 0.5 × MIC (p ≤ 0.001). Additionally, significant differences in outer membrane disruption were observed (p ≤ 0.05) with greater effects at 0.5 × MIC (p ≤ 0.005). Swarming motility was notably reduced for SA5 at 0.25 × MIC (p ≤ 0.05) and for PA2 at 0.5 × MIC (p ≤ 0.001). Chitinase activity showed greater reductions at 0.5 × MIC, with EC7 exhibiting the highest decrease. Lastly, sub-MIC concentrations enhanced reactive oxygen species (ROS) production, particularly for strains PA2 and SA5. Our results demonstrate the excellent potential of Dead Sea soil extract as an antimicrobial compound. Future studies should incorporate in vivo models to validate these findings clinically.